2023
DOI: 10.3389/fenvs.2023.1077181
|View full text |Cite
|
Sign up to set email alerts
|

Simulating basin-scale linkages of the food-energy-water nexus with reduced complexity modeling

Hussain H. Bokhari,
Ehsan Najafi,
Jorin Dawidowicz
et al.

Abstract: There is a rapidly growing need to communicate to the public and policymakers on the nature and impact of climate change and its associated extremes, which manifest themselves across essential Food-Energy-Water Systems (FEWS). The complexity of this nexus demands analytical tools that can capture the essence of FEWS with the climate system, which may be difficult to stage and implement from a computationally efficient point-of-view. Reduced Complexity Models (RCMs) can synthesize important facets of a system q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…With respect to digital elevation models, for example, the highest available resolutions are not always optimal for ecosystem modeling or terrain representation (e.g., [ 46 , 47 , 48 ]). Several studies have also found that, in addition to advantages in computational efficiencies and implementation costs, reduced-complexity models provide more accurate and useful results in many environmental modeling contexts (e.g., [ 9 , 10 , 11 , 12 , 49 , 50 ]).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to digital elevation models, for example, the highest available resolutions are not always optimal for ecosystem modeling or terrain representation (e.g., [ 46 , 47 , 48 ]). Several studies have also found that, in addition to advantages in computational efficiencies and implementation costs, reduced-complexity models provide more accurate and useful results in many environmental modeling contexts (e.g., [ 9 , 10 , 11 , 12 , 49 , 50 ]).…”
Section: Discussionmentioning
confidence: 99%